Little Riding Hood(s) Today: Theory, Editions and Practice in the University Classroom - Larragueta Arribas, Marta; Dotras Bravo, Alexia (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2020)
There is a big amount of materials on Little Red Riding Hood nowadays. There are philological, literary, historical, psychoanalytical or didactic studies, as well as multiple editions of the story, whether versions or adaptations. This abundance allows a wide variety of possibilities to approach this tale in the classroom. In this paper, we have first developed a detailed theoretical framework about the Little Red Riding Hoods currently available in the Spanish speaking countries, while paying special attention to picture books. Secondly, we have proposed different activities to perform the ongoing assessment of foreign university students who are taking children’s literature courses in Spanish, thus using the leitmotif of one of the most popular and universal children’s folktales.